Association of peak fever temperature with seizure incidence, recurrence, and clinical characteristics in children with febrile seizures excerpts from a single-centre prospective observational audit - Valiaveetil, Koshy Alan; Pazhani, Murugan Thimiri; Samuel, Melwin Dany (International Journal of Contemporary Pediatrics, 2026)
Background: Febrile seizures are the most common seizure disorder in early childhood and a frequent cause of paediatric emergency department visits. Fever height is often perceived as a key determinant of seizure risk, although evidence supporting this association remains inconsistent. To evaluate whether the height of fever at presentation is associated with the incidence or recurrence of febrile seizures in young children presenting to a paediatric emergency department. Methods: This was a single-centre descriptive observational audit conducted in a paediatric emergency unit over a one-month period. Children aged 11–48 months presenting with febrile seizures were included. Demographic data, seizure characteristics, maximum recorded body temperature, recurrence during the same illness episode, and management outcomes were collected. Mean fever temperatures between children with recurrent and non-recurrent seizures were compared using an independent t-test. Associations between categorical variables were analyzed using the Chi-square test. Results: Thirty children were included, with a mean age of 22.1 months; 73.3% were male. Typical febrile seizures accounted for 86.7% of cases. Recurrent seizures occurred in 36.7% of children. The mean fever temperature at presentation was 101.35°F. There was no statistically significant difference in fever height between children with recurrent and non-recurrent seizures (t=1.78, p=0.092). No significant association was observed between seizure type and gender. Most children were managed conservatively, with low rates of anticonvulsant use (13.3%) and hospital admission (13.3%). Caregiver counselling was provided in all cases. Conclusion: Fever height at presentation was not associated with seizure incidence or recurrence in children with febrile seizures. These findings support guideline-recommended conservative management and reinforce that absolute fever temperature alone should not influence clinical decision-making in uncomplicated febrile seizures.